Vagy soha? - Kis Pongrácz , Tamás (Kultúratudományi Szemle, 2022)
Or never? Tamás Kis Pongrácz Before I find the answer to the question: “Is there a particular relevance of the risk of apocalypse coming close, due to the pandemic?”, I try to clarify briefly how the notion of apocalypse changed through time. After that, in agreement with the spiritual evolutionism of Teilhard de Chardin and based on this theory I give reasons that human kind is not at the end of its road but it has started to grow adolescent and will truly deploy itself from now on.